1989
DOI: 10.1055/s-2007-1014609
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Pharmacokinetic Evaluation of Zuclopenthixol Acetate in Viscoleo®

Abstract: The purpose of the present study was to evaluate zuclopenthixol acetate in Viscoleo, a new preparation to be administered once every 3 days, in the early treatment of acute psychotic episodes and acute deterioration of chronic psychosis. 21 cases were included in the study: patients received 1 to 3 injections. Clinical evaluation was made at 24, 48 and 72 hours after each injection, using the Clinical Global Impressions (CGI) and the Brief Psychiatric Rating Scale (BPRS). Results at end-point indicated a marke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 4 publications
2
4
0
Order By: Relevance
“…The levels gradually fall from this time and are at approximately one-third of the peak level at 72 h [1]. A number of open studies have demonstrated a reduction in Brief Psychiatric Rating Scale [6] scores during the 3-day period of action, including scores on psychotic items such as hallucinatory behaviour and unusual thought content [7,8]. This is consistent with the proportion of dopamine receptor blockade that is usually associated with antipsychotic efficacy in typical neuroleptics [3][4][5].…”
supporting
confidence: 57%
“…The levels gradually fall from this time and are at approximately one-third of the peak level at 72 h [1]. A number of open studies have demonstrated a reduction in Brief Psychiatric Rating Scale [6] scores during the 3-day period of action, including scores on psychotic items such as hallucinatory behaviour and unusual thought content [7,8]. This is consistent with the proportion of dopamine receptor blockade that is usually associated with antipsychotic efficacy in typical neuroleptics [3][4][5].…”
supporting
confidence: 57%
“…Many neuropsychopharmacological drugs are used as racemic compounds, and their enantiomers differ markedly in their pharmacodynamic and pharmacokinetic properties [88,1104]. So far, however, methadone and methylphenidate are at present the only racemic psychotropic compounds for which TDM of the enantiomers has been introduced [68,322]. The active enantiomer of racemic methadone is (R)-methadone, and l-methylphenidate (i. e., levorotary methylphendiate) is primarily responsible for the therapeutic effect of racemic methylphenidate.…”
Section: Absorption Distribution and Elimination Of Neuropsychiatricmentioning
confidence: 99%
“…Two independently conducted open studies produced similar results with a slow onset of effect peaking at 24 hours and still being evident at 72 hours (Balant et al, 1989;Lowert et al, 1989). Thereafter, the first UK study reported that a significant reduction in psychosis score was first evident at 8 hours and scores continued to fall until the last measurement at 72 hours; of 25 participants assessed only four showed signs of tranquillisation at 1 hour, 19 participants at 2 hours and 22 participants at 24 hours (Chakravarti et al, 1990).…”
Section: Zuclopenthixol Acetatementioning
confidence: 79%